Design and Implementation of a Scalable LoRa-Based IoT Irrigation System with Dual Control Mechanisms - Salahedin Rehan; Esra Alhame; Esra Hassan (ITEGAM-JETIA)
Efficient water management is a critical challenge in large-scale agriculture, especially in remote areas where manual monitoring and control of irrigation systems are impractical. This paper presents the design and implementation of a scalable, LoRa-based Internet of Things irrigation system with dual control mechanisms, offering both local and remote control of irrigation processes. The system comprises field sensor nodes that transmit environmental data—such as soil moisture, temperature, and pump status—to both a local control node and a cloud gateway. Users can manage irrigation remotely via a cloud-based dashboard, while local control is achieved through manual intervention at the control node. A synchronization mechanism ensures that changes in actuator states are reflected across the system, regardless of where the control originates. By employing Long Range technology for extended communication distances and MQTT (Message Queuing Telemetry Transport) for efficient cloud connectivity, the system supports reliable, low-power operation over distances of up to 5.76 kilometers. Field tests validate its effectiveness, showcasing its potential to enhance water use efficiency in agriculture and reduce the need for constant human oversight in irrigation management. The scalable design ensures the system can adapt to various agricultural field sizes, making it practical for wide-area irrigation management.